Carbon Aerogels: a study with different models of the effect resorcinol/catalyst at different ratios after pyrolysis and the effect on textural properties - Fonseca-Correa, Rafael Alberto; Bastidas-Barranco, Marlon Jose; Giraldo, Liliana; Moreno-Piraján, Juan Carlos (European Journal of Chemistry, 2017)
Eight samples of carbon aerogels were prepared at various resorcinol/catalytic (R/C) ratios (ranging from 25 to 1500) and followed the changes in structure after pyrolysis. Isotherms of N2 to 77 K were determined to calculate the textural parameters using Dubinin-Astakhov (DA), Barret Joyner and Halenda (BJH), Non-Local Density Functional Theory (NLDFT) and Quenched Solid Density Functional Theory (QSDFT) models. The results generated two series of samples. In series I, a single type of pores developed (microporous, at low R/C weight ratio). Series II developed mesoporosity to top gears of R/C (> 400). The specific areas ranged from 64 to 990 m2/g. Additional models were applied to the materials synthesized, which allowed for adjustment to a system of “cylinder-slit” pores by applying the QSDFT kernel, with an error percentage ranging from 0.03 to 0.74.